Building Students’ Creativity in Writing through HOTS Learning - Novi Rahmania Aquariza (Universitas Muhammadiyah Surabaya, 2019)
In learning English, there are many ways to build students’ creativity in writing.Teachers out there have their own authority in designing methods and materials whichare commonly used to provoke it. Besides teachers can also use Higher Order Thinking(HOTS) learning design as a way to build students’ creativity in writing. Higher OrderThinking Skills include analysis, synthesis, evaluation and require mastery of previouslevels, such as applying routine rules to familiar or common problems (Keshta, 2013).The implementation of it in the learning process surely will be in line with the learningtarget. Nowadays, HOTS (Higher Order Thinking Skills) becoming more popularbecause it was clearly stated and used in last year National Exam. Thus, through thispaper I will discuss some HOTS activities in learning which can be used to buildstudents’ creativity especially in writing.Keywords: HOTS Learning, Writing.